Aspekty teoretyczne segmentacji regionalnej - Sobczak, Elżbieta (Theoretical Aspects of Regional Segmentation, 2007)
The objective of the hereby article is to identify the most important aspects of regional segmentation and its practical usefulness. Furthermore, factors of regional segments attractiveness and post-segmentation strategies of enterprise were presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 112-121